Pricing and quality strategies for an on-demand housekeeping platform with customer-intensive services - YU, Jianjun (Institutional Knowledge at Singapore Management University, 2022)
In this paper, we study an on-demand housekeeping platform in which suppliers have hetero-geneous opportunity costs, and customers are sensitive to service quality, price, and waitingtime. The platform charges fees from customers and divides revenue with service suppliers ina certain proportion. We analyze two types of market coverage, namely full market coverageand partial market coverage. We find that as the potential demand market capacity expands,the platform will choose to lower prices to attract more customers and service suppliers until itreaches the partial market, thereby obtaining higher revenue, and suppliers will provide lowerquality services to serve more customers and thus obtain more wages. Moreover, we showthat the partial market is more favorable to the platform than the full market. However, forservice suppliers, the partial market is not always more favorable. Meanwhile, as customersare more sensitive to the service value, suppliers will tend to lower their service rates toimprove service quality, and the platform will tend to set higher service prices. Interestingly, weobserve that when the sensitivity of service value is relatively small, the sensitivity of servicevalue has even the opposite effect on the platform's revenue and service suppliers' payoffs, aswell as the equilibrium number of service suppliers in different market scenarios. In addition,different market scenarios also will lead to the opposite effect of the service cost on the optimalequilibrium price, arrival rate, and service rate. However, the increase in the service cost willlead to a decrease in platform revenue and service supplier payoffs and the number of service suppliers in both market scenarios